Spectrum of β-Thalassemia Mutations in Some Areas of Guangxi Zhuang Autonomous Region of Southern China: A Study on a Pediatric Population Aged 0–15 Years. (3rd September 2021) - Huang, Li-Fang; Yu, Li-Li; Nikuze, Lauriane; Singh, Sanjeev; Jiang, Jin-Xia; Jiang, Jia-Li; Li, Yu-Ping; Qin, Yu-Hui; Wei, Hong-Ying
Abstract: β-Thalassemia (β-thal), one of the most common form of single-gene inheritable blood diseases in the world, is highly prevalent in southern China, especially in the Guangxi Zhuang Autonomous Region. To update the β-thal mutation spectrum in this region, we performed hematological and genetic analyses on 888 β-thal major (β-TM), β-thal intermedia (β-TI) and β-thal carrier patients, aged 0–15 years old, from different parts of Guangxi Province. We identified 55 genotypes and 18 β-thal mutations. The codons 41/42 (–TTCT) ( HBB : c.126_129delCTTT) (43.97%), codon 17 (A>T) ( HBB : c.52A>T) (25.43%), −28(A>G) ( HBB : c.-78A>G) (8.18%), IVS-II-654 (C>T) ( HBB : c.316-197C>T) (7.85%) and codon 26 (G>A) ( HBB : c.79G>A) (5.02%) were the five most common, accounting for more than 90.0%. The results of our study are providing an up-to-date β-thal mutation spectrum in the 0–15-year-old pediatric population, which will help genetic counseling and prevention of β-TM in mainland China's most endemic region, Guangxi Zhuang Autonomous Region.